IMPROVING THE EFFECTIVENESS OF VIDEOTHORACOSCOPY IN PEDIATRIC PULMONARY ECHINOCOCCECTOMIES - H.S, Usmanov; To‘raev , D.G‘ (Educational Research in Universal Sciences, 2024)
The aim of the work is to improve the results of surgical treatment of children with echinococcal lung disease by applying new technologies. Materials and methods of research. 72 children with echinococcal lung disease were operated on in RNPCMECDV during the period from 2005 to 2022. The main methods for diagnosing pulmonary echinococcosis were: chest X-ray examination, ultrasound, serologic reactions for echinococcosis (ELISA), MSCT of the thoracic organs. Translated with www.DeepL.com/Translator (free version) Results. Analysis of the results shows that echinococcal cysts with a diameter of more than 50 mm, as well as recurrent cysts complicated by suppuration, are considered as "relative" contraindications to videothoracoscopic echinococcectomy of the lung. Endovideosurgical echinocolectomy is and should be a priority in the treatment of pulmonary echinococcosis.